(untitled) (Almanack, 2024)
Obra resenhada: RÉ, Henrique Antônio; SAES, Laurent Azevedo Marques de; VELLOSO, Gustavo (org.). História e historiografia do trabalho escravo no Brasil: Novas perspectivas. São Paulo: Publicações BBM, 2020.